The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/jhep10(2011)039
|View full text |Cite
|
Sign up to set email alerts
|

The free energy of $ \mathcal{N} = 2 $ supersymmetric AdS4 solutions of M-theory

Abstract: We show that general N = 2 supersymmetric AdS 4 solutions of M-theory with non-zero M2-brane charge admit a canonical contact structure. The free energy of the dual superconformal field theory on S 3 and the scaling dimensions of operators dual to supersymmetric wrapped M5-branes are expressed via AdS/CFT in terms of contact volumes. In particular, this leads to topological and localization formulae for the coefficient of N 3/2 in the free energy of such solutions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…The free energy exhibits a scaling of N 3/2 where N is the rank of the gauge group with the exact numerical prefactor matching the regularized classical action of 11d SUGRA on AdS 4 × S 7 /Z k . Generalizations of this large N behavior were found for a large class of theories and the prefactor consistently matched the classical supergravity action of the dual M-theory on AdS 4 × X 7 , which is proportional to the volume of the compact X 7 [25][26][27][28][29][30].…”
Section: Localization In the Boundary Gauge Theory And The Airy Functionmentioning
confidence: 63%
“…The free energy exhibits a scaling of N 3/2 where N is the rank of the gauge group with the exact numerical prefactor matching the regularized classical action of 11d SUGRA on AdS 4 × S 7 /Z k . Generalizations of this large N behavior were found for a large class of theories and the prefactor consistently matched the classical supergravity action of the dual M-theory on AdS 4 × X 7 , which is proportional to the volume of the compact X 7 [25][26][27][28][29][30].…”
Section: Localization In the Boundary Gauge Theory And The Airy Functionmentioning
confidence: 63%
“…A contact form η always has an associated unique Reeb vector field ξ, defined via the equations ξ η = 1, ξ dη = 0, and in [24,25] it was shown that ξ is also the R-symmetry Killing vector field, 2 Similar Wilson loops have recently been considered in five-dimensional superconformal field theories on S 5 [43], which may also be computed using localization techniques. The gravity duals are described by warped AdS6 × S 4 /Zn solutions of massive IIA supergravity, and thus the geometry of the internal spaces here is fixed and in fact unique [44].…”
Section: Jhep01(2014)083mentioning
confidence: 99%
“…Since (1.4) depends only on η we may compute this expression in examples using the same methods employed in [24,25,45]- [49]. For example, for toric solutions (1.4) may be computed entirely using toric geometry methods.…”
Section: Jhep01(2014)083mentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the free energy, we evaluate the action (3.1) of the solution (3.2) with the boundary and counter terms [24,25] …”
Section: Jhep07(2014)061mentioning
confidence: 99%